Analisis Data Mining Menentukan Penerima Bantuan Langsung Tunai pada Desa Pamatang Purba dengan Algoritma C 4.5 - Rajes Wasimson Sinaga; Riki Winanjaya; S Susianti (LPPM STIKOM Tunas Bangsa, 2021)
In tackling the problem of poverty, the Government implements a cash direct assistance program (BLT) which is a program that provides cash assistance (subsidies) to poor households if they meet the requirements set out in the program. The purpose of this study is to determine whether the family is still eligible or does not receive direct cash assistance (BLT), where there are still many other poor families who have not had the opportunity to receive this assistance program. Data source obtained from The Office of Lurah Pamatang Purba. The method used in the study was data mining technique with C4.5algorithm that was impelemented with RapidMiner application. The attributes used in determining the eligibility of the family are still eligible or do not receive assistance in this assistance program, namely income, age, marital status, employment, recipients of Bansos, bpjs recipients. The results of the classification using the C4.5 algorithm and testing with softwareRapidMiner is the most influential factor in the eligibility of recipients of the direct cash assistance program (BLT)